Wind Characteristics Influencing Wind Energy. - Chiang, E.P.; Bawadi, M. A.; Narayana, P.A. Aswatha; Zainal, Z. A.; Seetharamu, K. N. (2003)
Usually the wind speed for a particular site is given at a standard reference height of 10m. However, in the context of wind turbines, the hub height is a natural choice for estimating the power potential.